Myeloperoxidase: A New Biomarker of Inflammation in Ischemic Heart Disease and Acute Coronary Syndromes - Loria, Valentina (Hindawi Publishing Corporation, 2008)
Myeloperoxidase (MPO) is an enzyme stored in azurophilic granules of polymorphonuclear neutrophils and macrophages and released into extracellular fluid in the setting of inflammatory process. The observation that myeloperoxidase is involved in oxidative stress and inflammation has been a leading factor to study myeloperoxidase as a possible marker of plaque instability and a useful clinical tool in the evaluation of patients with coronary heart disease. The purpose of this review is to provide an overview of the pathophysiological, analytical, and clinical characteristics of MPO and to summarize the state of art about the possible clinical use of MPO as a marker for diagnosis and risk stratification of patients with acute coronary syndrome (ACS).